THE INFLUENCE OF EMPLOYEE COMPETENCE, ORGANIZATIONAL COMMITMENT AND IMPLEMENTATION OF ACCOUNTING SYSTEMS ON THE QUALITY OF FINANCIAL REPORTS WITH EMPLOYEE MOTIVATION AS VARIABLE MODERATING IN BAPPEDA KEPRI PROVINCE - Wahyuni, Sri; Wibisono, Chablullah; Robin, Robin; Satriawan, Bambang; Irfan, Irfan (RADJA PUBLIKA, 2022)
This study aims to examine the effect of employee competence, organizational commitment and accounting system implementation on the quality of financial reports with motivation as a moderating variable in Bappeda Riau Islands Province. This study uses secondary data. This study used a saturated sampling technique with a total sample of 104 companies. The data analysis technique used is the SEM method with the help of the PLS program with Smartpls 3.0 software. Based on the test results, it is known that employee competency with respect to the variable quality of financial statements obtained a path coefficient of 0.185 with a statistical value of 2.519 (> 1.64) and a p-value of 0.012 (<0.05). Because the t-statistic value must be more than 1.64 and the p-value <0.05, the first hypothesis (H1) is accepted. The next result is organizational commitment to the quality of financial reports obtained by a path coefficient of 0.101 with a statistical value of 1.081 (<1.64) and a p-value of 0.280 (> 0.05). because the t-statistic value must be more than 1.64 and the p-value <0.05, the hypothesis (H2) is rejected. Then the application of the accounting system to the quality of financial reports obtained a path coefficient of 0.019 with a statistical value of 10.518 (> 1.64) and a p-value of 0.000 (< 0.05). because the t-statistic value must be more than 1.64 and the p-value <0.05, the hypothesis (H3) is accepted. Furthermore, employee motivation on the quality of financial reports moderated by employee motivation obtained a path coefficient of 0.0165 with a statistical value of 1.370 (<1.64) and a p-value of 0.171 (> 0.05). Because the t-statistic value must be more than 1.64 and the p-value <0.05, the hypothesis (H4) is rejected. organizational commitment to the quality of financial reports moderated by employee motivation obtained a path coefficient of -0.043 with a statistical value of 0.593 (<1.64) and a p-value of 0.554 (> 0.05). because the t-statistic value must be more than 1.64 and the p-value <0.05, the hypothesis (H5) is rejected. The application of the accounting system to the quality of financial reports moderated by employee motivation obtained a path coefficient of -0.076 with a statistical value of 0.709 (<1.64) and a p-value of 0.479 (> 0.05). because the t-statistic value must be more than 1.64 and the p-value <0.05, the hypothesis (H6) is rejected. organizational commitment to the quality of financial reports moderated by employee motivation obtained a path coefficient of -0.043 with a statistical value of 0.593 (<1.64) and a p-value of 0.554 (> 0.05). because the t-statistic value must be more than 1.64 and the p-value <0.05, the hypothesis (H5) is rejected. The application of the accounting system to the quality of financial reports moderated by employee motivation obtained a path coefficient of -0.076 with a statistical value of 0.709 (<1.64) and a p-value of 0.479 (> 0.05). because the t-statistic value must be more than 1.64 and the p-value <0.05, the hypothesis (H6) is rejected. organizational commitment to the quality of financial reports moderated by employee motivation obtained a path coefficient of -0.043 with a statistical value of 0.593 (<1.64) and a p-value of 0.554 (> 0.05). because the t-statistic value must be more than 1.64 and the p-value <0.05, the hypothesis (H5) is rejected. The application of the accounting system to the quality of financial reports moderated by employee motivation obtained a path coefficient of -0.076 with a statistical value of 0.709 (<1.64) and a p-value of 0.479 (> 0.05). because the t-statistic value must be more than 1.64 and the p-value <0.05, the hypothesis (H6) is rejected. because the t-statistic value must be more than 1.64 and the p-value <0.05, the hypothesis (H5) is rejected. The application of the accounting system to the quality of financial reports moderated by employee motivation obtained a path coefficient of -0.076 with a statistical value of 0.709 (<1.64) and a p-value of 0.479 (> 0.05). because the t-statistic value must be more than 1.64 and the p-value <0.05, the hypothesis (H6) is rejected. because the t-statistic value must be more than 1.64 and the p-value <0.05, the hypothesis (H5) is rejected. The application of the accounting system to the quality of financial reports moderated by employee motivation obtained a path coefficient of -0.076 with a statistical value of 0.709 (<1.64) and a p-value of 0.479 (> 0.05). because the t-statistic value must be more than 1.64 and the p-value <0.05, the hypothesis (H6) is rejected.